Analysis of the association between human papillomavirus with penile carcinoma - Gil, A. O.; Pompeo, A. C.L.; Goldstein, P. J.; Saldanha, L. B.; Mesquita, J. L.B.; Arap, S. (My University, 2001)
Objective: To determine the incidence and which type of human papillomavirus (HPV) was more prevalent in penile epidermoid carcinoma. To determine the influence of HPV in the biological behavior of the tumor in relation to the following variables: coilocitosis, clinical and pathological staging and histological grading. Prognostic factors like survival curve and death risk from the tumor are also studied in relation to the presence of HPV. Material and Methods: Fifty-five patients with penile epidermoid carcinoma, surgically treated between 1979 and 1995, were retrospectively studied. The mean follow-up was 31.6 months. The presence of HPV was studied by polymerase chain reaction (PCR) on the most representative surgical specimens of the primary tumor and metastasis. The patients whose tumors had HPV type-16 were placed into groups separated from those uninfected by the virus and those infected by any other viral type. Results: Patients having HPV type-16 in their tumors were submitted to major surgical procedures to remove the primary tumor (p = 0.04). The relative risk of death for patients with HPV type-16 was 7.59 times greater than that for the virus negative group. Also, patients presenting HPV type-16 in the tumor presented a lower tendency for survival (without statistical significance). Coilocitosis was detected in 12 patients, presenting a significant correlation with the presence of HPV type-16 (p = 0.026). Conclusion: The infection by HPV was strongly associated with penile epidermoid carcinoma (30.9%). Also, the presence of coilocitosis is strongly associated with viral infection. The presence of HPV type-16 in the tumors was associated with increased tumor-related mortality.
Keywords: Epidermoid carcinoma; Human papillomavirus; Penile carcinoma; Penis; Tumors